Áhrif náttúrubaða á andlega og líkamlega líðan ferðamanna - Sigríður Kristín Sigþórsdóttir 1993- (2018)
Breathtaking nature is Iceland’s fundamental main attraction for tourism and is considered an essential element in the business of Icelandic tourism. This essay analyzes the findings of research conducted regarding the experiences of foreign tourists in Iceland to see whether they report changes in their physical and spiritual state after spending time in nature baths. The study was executed in the nature baths at Laugarvatn Fontana, which is near Laugarvatn where ten tourists were interviewed and asked about their expectations and experiences at Laugarvatn Fontana nature baths. Furthermore, the interviewees were inquired about which aspects of the nature baths appealed to them, how they experienced their physical and mental state during the time spent in the baths, and whether they reported noticeable difference post-bathing. Moreover, a participation survey was conducted regarding the situation on the day of the interviews. The study showed that every participating individuals expresses’ a positive change and difference in their physical, mental and spiritual state. There were also indications that there is a strong connection between visual aesthetics of the surrounding nature at Laugarvatn Fontana coupled with the physical enjoyment of the nature baths. The results suggest that it is possible to assume that the organization and design of such a place must be executed with the aim to provide an unhindered access to the landscape and outdoor activities because of the hugely important role it plays regarding the nature baths rejuvenating effect and positive effect experienced whilst in the baths.